Endovascular techniques for achievement of better flow diverter wall apposition. Issue 3 (June 2019) - Kühn, Anna L; Rodrigues, Katyucia de Macedo; Wakhloo, Ajay K; Puri, Ajit S
Flow diverter malapposition has been described as a technical complication during endovascular procedures and can be associated with, potentially delayed, life-threatening aneurysm rupture or ischemic events. We performed a retrospective review of our flow diverter database to identify all patients in whom device malapposition was detected on follow-up angiogram immediately after device deployment. Feasibility and technical success of different endovascular approaches aiming to correct the inadequate vessel wall apposition were evaluated. Successful endovascular techniques for manipulation of the flow diverter included use of wires, catheters and additional flow diverter/stent devices. In our practice, we found six successful endovascular techniques for device manipulation, which allowed us to safely achieve good flow diverter wall apposition.